The First Case Report of Kabuki Syndrome from the National Iranian Registry of Primary Immunodeficiencies - Safarirad, Molood; Ganji, Ali A.; Fekrvand, Saba; Yazdani, Reza; Motlagh, Ahmad Vosughi; Abolhassani, Hassan; Aghamohammadi, Asghar (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Kabuki syndrome is a rare congenital anomaly/mental retardation syndrome characterized by intellectual disability, developmental delay, short stature, facial dysmorphic features including ectropion of the lateral third of the lower eyelids, long palpebral fissures, and prominent finger pads. Pathogenic variants of KMT2D (MLL2) and KDM6A are found to be the major causes of Kabuki syndrome. Here, we report the first Iranian case with Kabuki syndrome with an IQ of 79, two episodes of viral pneumonia and distinctive facial features, prominent ears, and persistent fetal fingertip pads. These characteristics raised our suspicion of performing whole-exome sequencing (WES), which revealed 2 heterozygous pathogenic missense variants in the KMT2D gene: c.C10024T in exon 34, leading to p.R3342C and c.G15005A in exon 48, leading to p.R5002Q. Hence, the definitive diagnosis of Kabuki syndrome was made based on molecular findings along with the intellectual disability and characteristic facial features.
Keywords: facial dysmorphic features